Managing Soils for Recovering from the COVID-19 Pandemic - Rattan Lal; Eric C. Brevik; Lorna Dawson; Damien Field; Bruno Glaser; Alfred E. Hartemink; Ryusuke Hatano; Bruce Lascelles; Curtis Monger; Thomas Scholten; Bal Ram Singh; Heide Spiegel; et al. (Soil Systems, 2020)
The COVID-19 pandemic has disrupted the global food supply chain and exacerbated the problem of food and nutritional insecurity. Here we outline soil strategies to strengthen local food production systems, enhance their resilience, and create a circular economy focused on soil restoration through carbon sequestration, on-farm cycling of nutrients, minimizing environmental pollution, and contamination of food. Smart web-based geospatial decision support systems (S-DSSs) for land use planning and management is a useful tool for sustainable development. Forensic soil science can also contribute to cold case investigations, both in providing intelligence and evidence in court and in ascertaining the provenance and safety of food products. Soil can be used for the safe disposal of medical waste, but increased understanding is needed on the transfer of virus through pedosphere processes. Strengthening communication between soil scientists and policy makers and improving distance learning techniques are critical for the post-COVID restoration.